(3GdebUO dJdNjU eG aj GdeQTOs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3CHh eMeO GdMSf Hf Ydj Hf SYjO GdfYeGfjs
(3ChdgG (B:s
(3GdMeO ddg Ydi BdGFI hHYO agPG eNJUQ GdeQTO ai Gdhba hGdEHJOGA GdPi Cdag CHh eMeO GdMSf Hf Ydi hbO EdJRe Cf jhQO ajg LejY eG ChQOg Cgd gPG Gdaf hSejJg GdebUO hCbhd (B: (3Gdhba s
(3BNQgG (B:s
(3ShQI Gdadb djS ajgG hba cGma hdG JGe ZdG BNQgG NJGe bGdg (B: (3CHh YeQh hGdfGS hba MSf Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs